PENGARUH FAKTOR-FAKTOR FUNDAMENTAL DAN REPUTASI UNDERWRITER TERHADAP UNDERPRICING PADA PERUSAHAAN YANG MELAKUKAN IPO PERIODE 2006-2011 - Pakpahan, Rosma (Universitas Pendidikan Indonesia, 2015)
Underpricing phenomenon that often occurs in almost all capital markets in the world including in Indonesia is due to information asymmetry between issuers , underwriters and investors ( Beatty , 1989) , Guinness (1992 ) . Dissimilarity information owned issuers , underwriters and investors lead IPO price difference ( primary market ) and therefore caused underpricing . This is a different impact for corporate issuers and investors . Issuer will not benefit in the event of underpricing , because the proceeds from going public / IPO not optimally achieved . While investors will benefit from gaining initial returns ( profits early / prime profit ) is the difference between the IPO price in the primary market with a closing stock price on the first day of listing on the secondary market ( IDX ) . Several studies have been conducted and the results are diverse , Sandhiaji (2004 ) , Yolana and Martani (2005 ) and Gerianta (2008 ) .This study proposed six hypotheses that underwriter reputation , DER , ROA , firm size and value offers simultaneous and partial significantly affect the initial return as a proxy of underpricing . However, the results showed no statistically supported the research hypothesis .Keywords : underwriter reputation , DER , ROA , firm size ,market prices, initial returns ( underpricing)